Penyaluran Kredit MESRA (Masyarakat Ekonomi Sejahtera) Pada Usaha Mikro - Marlina Nur Lestari; Toto Toto; Risna Kartika; Andini Grace Tinia (Politeknik Ganesha Medan, 2023)
MSME actors in Indonesia account for 99% of the number of business actors in Indonesia and give 61.1% for GDP, then stakeholders in Indonesia must strive to be able to renew MSMEs in order to increase GDP. One of these efforts is to provide soft credit to MSMEs to encourage an increase in business scale. Bank BJB Ciamis has a MESRA (Prosperous Economic Community) lending program, one of goals is to place MSMEs. The purpose of this study was to determine the magnitude of the influence of MESRA's credit on increasing the scale of micro-enterprises (Studies at Bank BJB Ciamis Branch). This research is quantitative with two research variables, namely MESRA's credit distribution (X) and increasing the scale of micro-enterprises (Y). The data used is secondary data on the research subject of Bank BJB Ciamis Branch. The research sample is MESRA's credit data enrichment and the level of sales in MSMEs in 2019 – 2022. The analysis technique used is simple regression analysis. This study produces a large effect of 94% with a positive correlation. The result of testing the hypothesis is the F test of 1.72% <5%, which means that the proposed hypothesis is accepted (significant). The conclusion from this study is that MESRA's credit has a positive effect on increasing the scale of micro-enterprises (a study at Bank BJB Ciamis), which means that the higher the level of MESRA's credit then the greater the scale of micro-enterprises.